2018
DOI: 10.1523/jneurosci.1458-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Elicits Behavioral Responses through Mechanical Effects on Neurons and Ion Channels in a Simple Nervous System

Abstract: Focused ultrasound has been shown to stimulate excitable cells, but the biophysical mechanisms behind this phenomenon remain poorly understood. To provide additional insight, we devised a behavioral-genetic assay applied to the well-characterized nervous system of nematodes. We found that pulsed ultrasound elicits robust reversal behavior in wild-type animals in a pressure-, duration-, and pulse protocol-dependent manner. Responses were preserved in mutants unable to sense thermal fluctuations and absent in mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
211
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 243 publications
(221 citation statements)
references
References 63 publications
10
211
0
Order By: Relevance
“…It has been found that mutants that lack a pore-forming subunit of an ion channel that is critical for sensing gentle touch show a profound deficit in the responsiveness to FUS. 31 Thus, a mechanosensitive ion channel is required for the FUS response in this animal. Patch-clamp recordings in another recent study further revealed FUS effects on ion channels of the Piezo family.…”
Section: Mechanism Of Ultrasonic Neuromodulationmentioning
confidence: 89%
See 4 more Smart Citations
“…It has been found that mutants that lack a pore-forming subunit of an ion channel that is critical for sensing gentle touch show a profound deficit in the responsiveness to FUS. 31 Thus, a mechanosensitive ion channel is required for the FUS response in this animal. Patch-clamp recordings in another recent study further revealed FUS effects on ion channels of the Piezo family.…”
Section: Mechanism Of Ultrasonic Neuromodulationmentioning
confidence: 89%
“…It has been hypothesized that these effects are mediated by ion channels that can detect changes in membrane stretch following a propagating pressure wave. 30,31,49,57,58 Other mechanisms may also be at play; this topic is discussed in more detail below. Besides transient effects, FUS applied for a substantial time period (> 10 seconds) can induce long-term changes in neural activity of the stimulated circuits.…”
Section: Transcranial Focused Ultrasoundmentioning
confidence: 99%
See 3 more Smart Citations